Targeting in development Projects: Approaches, challenges, and lessons learned - Kurdi, Sikandra (International Food Policy Research Institute, 2023)
These set of slides were presented at the BEP Seminar "Targeting in Development Projects: Approaches, challenges, and lessons learned" held last Oct. 2, 2023 in Cairo, Egypt